(untitled) (Economics and region, 2021)
The article considers the role of integration processes of the quality management system in the field of civil aviation. The process of effective implementation of IMS in the corporate environment is taken into consideration and substantiated. The analysis of ICAO-9859 Document is carried out and the need for the implementation of an integrated corporate management system in organizations operating in civil aviation is described. The advantages of using integrated systems are distinguished. General and specific principles of the Safety Management System (SMS) and Quality Management System (QMS) are highlighted. The created system for the effective implementation of the IMS is considered using a specific example of applying the requirements of the “Safety Management Manual”